(untitled) (Bangladesh Journal of Medical Science, 2020)
Choriocarcinoma is a malignant trophoblastic disease. It can be divided into gestational and non-gestational type. Gestational choriocarcinoma consists of less than 1% of total endometrial malignancy, and usually is diagnosed via histopathological examination preceding a suspected molar pregnancy. In contrast to gestational choriocarcinoma, only a few cases of primary non-gestational choriocarcinoma were reported in literature reviews. The reported locations for primary non-gestational choriocarcinoma were ovarian and uterine cervix. Due to its low incidence, this disease is often overlooked leading, to delayed diagnosis. In primary care practice, heavy menstrual bleeding is a common presentation. Further evaluations, such as full blood count, ultrasound pelvis or hysteroscopy are usually required. We would like to report a case of potentially earlier detection of non-gestational choriocarcinoma in a 52 years old lady who was presented with heavy menstrual bleeding for a duration of one year. Her symptom persisted despite receiving medical treatment in a few local primary care clinics. She was admitted to a tertiary hospital for symptomatic anaemia which required blood transfusion. Further evaluations, (i.e., laboratory tests, ultrasound, Computed Topography (CT) scan, bone scan, hysteroscopy and laparotomy total abdominal hysterectomy and bilateral salphingo-oophorectomy (TAHBSO) and histological examination) concluded a diagnosis of primary non-gestational choriocarcinoma of fundal uterus with lung metastasis. Bangladesh Journal of Medical Science Vol.19(4) 2020 p.755-759